Dissemination of Mechanisms for Handling Criminal Cases in Criminal Procedure Law - Juanrico Alfaromona Sumarezs Titahelu (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Crime is a social symptom of society. Crime grows and develops along with the growth and development of society. Policies in the use of criminal law are closely correlated with criminalization.Purposes of Devotion: Provide understanding to the community in Kilo 9 Village, Kawatu Hamlet, West Seram Regency (SBB), about the mechanism of handling cases of general crimes in Criminal Procedure Law. Method of Devotion: Conducting surveys and discussions to obtain the information needed and set goals in socialization activities. At the preparatory stage is also carried out preparing the material.Results of the Devotion: The implementation of community service activities in the village of RTKilo 9, West Seram district (SBB), can be found and it is known that the mechanism of handling cases in Criminal Procedure Law, including; preliminary examination stage examination stage in the trial, the stage of Criminal implementation, especially criminal Agency of Inter-Institutional Relations in the process of resolving cases and criminal case settlement Model according to Restorative Justice, consists of Victim-Offender Reconciliation or Mediaton Programs (VORP), Sentencing circles or Healing circles, and Prisoner Assistance Programs.